Biodegradation of Palm Kernel Cake with Multienzyme Complexes from Fungi and its Feeding Value for Broilers - Lawal, T.E.; Iyayi, E.A.; Adeniyi, B.A.; Adaramoye, O.A. (International Journal of Poultry Science, 2010)
Palm Kernel Cake (PKC) was used as a substrate to elicit the production of polysaccharidases from Aspergillus niger, Trichoderma viride, Rhizopus stolonifer and Mucor mucedo. The extracted enzymes produced were purified and used to ferment PKC in solid state at the rate of 250 ml/kg of the material for 7 days. Unbiodegraded and enzyme degraded PKC were used to formulate broiler starter and finisher diets at the rates of 70 g kg-1 and 100 g kg-1, respectively. A 6th diet was formulated in which Roxazyme G2G, a commercial enzyme was used to supplement the unbiodegraded PKC at the recommended inclusion level of 0.15 g kg-1. A total of 360 1-d-old broiler chicks were randomly allocated to the 6 treatments of 6 replicates each with each replicates having 10 birds. Cellulose and hemicellulose were significantly (p